The value of the Caci dance performance: changing the perspective of cultural violence on fighting dance performances in Manggarai Indonesia - Maria Paskalia Aninda; Lambok Hermanto Sihombing (ASSOCIATION FOR SCIENTIFIC COMPUTING ELECTRICAL AND ENGINEERING (ASCEE), 2022)
Caci dance is one of the traditional fighting dances that is unique and contains an intense value. Caci is often displayed during traditional events of the Manggarai tribe. This shows that Caci is an essential part of the journey of the Manggarai community. Caci dance is now widely known because of its uniqueness and because the dance moves are hazardous because they contain physical violence; this is undoubtedly very interesting to study more deeply. The main problem is How the value of Caci reduces the perspective of Violence in Caci perceived by the audience. This study aims to determine the values that exist in the Caci dance and how the true meaning of Caci is so that it can change the perspective of the broader community that Caci is not only a dance that teaches physical violence. This descriptive qualitative research is located in Lentang Village, Lelak District, Manggarai Regency. Data was collected directly from local sources through interviews with traditional leaders and conducting a content analysis on YouTube channels categorised as having many viewers, national television channels, and Caci performances. This study shows that the art of Caci dance does not teach physical violence. Still, Caci has strong historical values and influences the social life of the Manggarai community. Caci has a definite philosophical meaning, showing the character of the Caci players. In conclusion, the values contained in Caci can strengthen socio-cultural values in the Manggarai community, in this case, significantly able to maintain the existence of Caci dance as a cultural identity with the values of life contained in it